2003
DOI: 10.1098/rspb.2003.2399
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of complex flowering strategies: an age– and size–structured integral projection model

Abstract: We explore the evolution of delayed age- and size-dependent flowering in the monocarpic perennial Carlina vulgaris, by extending the recently developed integral projection approach to include demographic rates that depend on size and age. The parameterized model has excellent descriptive properties both in terms of the population size and in terms of the distributions of sizes within each age class. In Carlina the probability of flowering depends on both plant size and age. We use the parameterized model to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 44 publications
1
129
1
Order By: Relevance
“…Most studies of reproduction in modular organisms emphasize the age or size dependence of reproduction (Law 1983, Lacey 1986, Klinkhamer et al 1992, Kapela and Lasker 1999, Childs et al 2003, Burd et al 2006. Our results are a clear departure from these studies because the reproductive characteristics of W. subtorquata are not determined by colony size or age.…”
Section: Discussioncontrasting
confidence: 90%
“…Most studies of reproduction in modular organisms emphasize the age or size dependence of reproduction (Law 1983, Lacey 1986, Klinkhamer et al 1992, Kapela and Lasker 1999, Childs et al 2003, Burd et al 2006. Our results are a clear departure from these studies because the reproductive characteristics of W. subtorquata are not determined by colony size or age.…”
Section: Discussioncontrasting
confidence: 90%
“…The vast majority of IPMs have been constructed phenomenologically, using statistical descriptions of observational data. Several authors have shown how fixed and random effects incorporated into these statistical functions can be formulated within IPMs (Childs et al 2003;Rees and Ellner 2009;Coulson 2012), but additional statistical estimation is required to parameterize the evolutionarily explicit IPMs we have developed. Fitness functions in evolutionarily explicit IPMs can be parameterized using standard general, generalized, and additive regression methods that are routinely used to parameterize phenomenological IPMs (Rees and Ellner 2009).…”
Section: Parameterizing and Analyzing Evolutionarily Explicit Ipmsmentioning
confidence: 99%
“…In these cases, standard nonevolutionarily explicit IPMs have accurately captured observed dynamics (Childs et al 2003;Ozgul et al 2010;Merow et al 2014).…”
Section: When Should Evolutionarily Explicit Ipms Be Used To Predict mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is rapidly gaining in popularity because of its obviously utility (Godfray and Rees 2002, Metcalf et al 2003, Rose et al 2005, Williams and Crone 2006, Kuss et al 2008, Zuidema et al 2010. Reanalysis of data previously used in matrix models provides additional ecological insights (e.g., Easterling et al 2000) and has greatly improved our understanding of how complex local demographic processes, and the associated individual variation, affect population growth and the evolution of life history strategies (Rees and Rose 2002, Childs et al 2003, Ellner and Rees 2006.…”
Section: Introductionmentioning
confidence: 99%